Monitoreo en tiempo real del consumo de energía eléctrica residencial que permita optimizar la eficiencia energética - Pérez Párraga, Roger Steven (2019)
The research project focuses on the creation of prototypes of an electrical system to obtain real-time data on the consumption of electricity in residential homes by obtaining samples that will be presented in an IoT-based application. This project consists of coil-type sensors that are responsible for collecting electricity consumption data and sending it to a Raspberry Pi so that it can be processed and stored in a time series database, while the data is transferred to an application web through communication protocols so that users can monitor the electrical consumption, observing the maximum values of an electrical circuit in real time, during a certain period of time according to the user's disposition. For the collection of data it was necessary to place the electrical system inside a box so that all the components are in a stable position and, therefore, at the moment when the sensors perform the monitoring, no erroneous data is obtained.